Physiological, but not fitness, effects of two interacting haemoparasitic infections in a wild rodent - Taylor, Christopher H.; Wanelik, Klara M.; Friberg, Ida M.; Lowe, Ann; Hall, Amy J.; Ralli, Catriona; Birtles, Richard J.; Begon, Mike; Paterson, Steve; Jackson, Joseph A.; Bradley, Janette E. (Elsevier, 2018)
In contrast to the conditions in most laboratory studies, wild animals are routinely challenged by multiple infections at once, and these infections can interact in complex ways. This means that the impact of a parasite on its host’s physiology and fitness cannot be fully assessed in isolation, and requires consideration of the interactions with other co-infections. Here we examine the impact of two common blood parasites in the field vole (Microtus agrestis): Babesia microti and Bartonella spp., both of which have zoonotic potential. We collected longitudinal and cross-sectional data from four populations of individually tagged wild field voles. This included data on biometrics, life history, ectoparasite counts, presence/absence of microparasites, immune markers and, for a subset of voles, more detailed physiological and immunological measurements. This allowed us to monitor infections over time and to estimate components of survival and fecundity. We confirm, as reported previously, that B. microti has a preventative effect on infection with Bartonella spp., but that the reverse is not true. We observed gross splenomegaly following B. microti infection, and an increase in IL-10 production together with some weight loss following Bartonella spp. infection. However, these animals appeared otherwise healthy and we detected no impact of infection on survival or fecundity due to the two haemoparasite taxa. This is particularly remarkable in the case of B. microti which induces apparently drastic long-term changes to spleen sizes, but without major adverse effects. Our work sheds light on the ecologies of these important zoonotic agents, and more generally on the influence that interactions among multiple parasites have on their hosts in the wild.